Can microteaching inform reflective practice?. Issue 1 (1st December 2022) - Taylor, Charles Frederick Collins; Border, Scott
Abstract : Microteaching was first introduced by Dwight W. Allen in the sixties and since then it has become a pivotal aspect of teacher training, particularly within medical education. As a form of teacher training, it enables teachers to reflect upon effective practice by implementing a deliberate cyclical reflection process. The importance of such reflective practice within medical education is well established. However, rarely is it regularly or successfully undertaken and the traditional 'see one, do one teach one' approach to teaching and training is widely disputed and in need of revival so that it may better reflect the shifting cultural, social and political restrictions and expectations placed on medical professionals. A plan, do, reflect, re-plan, re-do and re-reflect schema as adapted from the practice of microteaching provides a clear framework on how best to reflect on one's own practice and therefore acts as a positive initial step towards improving self-reflection within medical education.